Accountability and the fairness bias in the context of joint production: Effects of bonuses and opportunities - Alice Becker (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
According to the accountability principle a person's fair allocation takes into account the input-relevant variables she can influence, like effort, but not the variables she cannot influence, like a randomly assigned exogenous factor. This study is based on a real effort-task experiment, where the exogenous influence is twofold: it comes either as a production factor or as a bonus. We confirm that in a base treatment, i.e in absence of exogenous factors, subjects base their allocation decisions largely on effort. When exogenous differences are present behavior changes. Whereas bonuses are largely ignored and subjects still mostly base their decisions on effort, production factors render allocations more selfish. Furthermore, we study whether accountability holds for decisions over opportunities. We apply the so-called lottery-points-method, where a binary lottery in the last experimental stage allocates the whole amount to one of the workers. We find that subjects claim more for themselves when allocating opportunities in all treatments.
Keywords: C72; C92; 330; distributive justice; real effort task; procedural fairness; Verteilungsgerechtigkeit; Test; Gerechtigkeit; Bias; Leistungsentgelt